2019
DOI: 10.2147/jpr.s205570
|View full text |Cite
|
Sign up to set email alerts
|

<p>Practical approach to a patient with chronic pain of uncertain etiology in primary care</p>

Abstract: Chronic pain of uncertain etiology often presents a challenge to both patients and their health care providers. It is a complex condition influenced by structural and physiological changes in the peripheral and central nervous systems, and it directly influences, and is modulated by, psychological well-being and personality style, mood, sleep, activity level and social circumstances. Consequently, in order to effectively treat the pain, all of these need to be evaluated and addressed. An effective management s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Treatment of chronic pain is complicated and often results in inadequate response or side effects. Attempts are ongoing for a better understanding of pain processes, mechanism-based treatment and targeting, implications of multidisciplinary pain management, and patient-centered strategies ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of chronic pain is complicated and often results in inadequate response or side effects. Attempts are ongoing for a better understanding of pain processes, mechanism-based treatment and targeting, implications of multidisciplinary pain management, and patient-centered strategies ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pain which lasts less than 3 months is (how to cite article) stated as acute pain [10] and the pain that persist beyond the normal time expected for tissue healing (that is 3 months) is known as chronic pain. [11] In the current study the severity of the pain is measured by NRS and maximum number of male gym instructors had more amount of moderate to severe type of pain as compared to female gym instructors [figure 5]. Many studies were conducted regarding the pain tolerance in gender, two of the studies confirm that women are at higher risk for developing pain disorders and women show high sensitivity towards noxious stimuli.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, Sekar et al [ 29 ] showed dietary SFA could contribute to pain in mice with osteoarthritis via underlying mechanisms which are related to pro-inflammatory markers like interleukin-1β and interferon-γ. Fried foods are often prepared with plant oils which are rich in PUFAs (mostly omega 6) in Iran, and this can aggregate pain [ 30 ]. Oxidized linoleic acid derived mediators like oxylipins may be relevant to pain signaling and adaptation to chronic pain in the brain [ 31 ].…”
Section: Discussionmentioning
confidence: 99%